Public policies for sustainable regional development and environmental preservation in the Amazon context: A focus on the Tupé RDS in Amazonas (Research, Society and Development, 2021)
This article is an integral part of a master's research by the Postgraduate Program in Education at the Federal University of Amazonas (PPGE/UFAM), financed by the Coordination for the Improvement of Higher Education Personnel - CAPES and the State of State Research Support Foundation Amazonas - FAPEAM. Its objective is to analyze Public Policies for sustainable regional development and environmental preservation in the Amazon context, from the standpoint of the Tupé Sustainable Development Reserve in the State of Amazonas. Outlined by the qualitative approach and supported by the dialectical method that made it possible to understand the phenomena and their contradictions, it also had the aid of bibliographical and documentary research. It was found that the Management Plan of the Tupé RDS presents contradictions in relation to the Amazonian reality. The study points to the need for the Tupé RDS Management Plan to dialogue with public policies for sustainable regional development and environmental preservation in the Amazon context, enabling the reserve's residents to work, live, study and have the right to a dignified life in your place of origin.